Pengaruh Kreativitas Dan Inovasi Terhadap Keputusan Pembelian Konsumen Dalam Bisnis Internasional - Mutyara KD Chairunissa Pohan; Hendra Ibrahim (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
The increasingly rapid development of the business world causes companies to face intense competition. Seeing this, the company is of course aware that the level of business competition in the era of globalization and information technology which continues to experience increasingly intense changes, this of course creates business competition for business people that is becoming increasingly tighter and more difficult, so that many business people are competing to own and develop each other's efforts. As the business world develops, consumer needs become more diverse, without limitations and more creative and innovative, for this reason business actors are required to develop creativity and innovation in running their businesses in order to keep up with developments in consumer needs. The aim of this research is to find out how much influence creativity and innovation have on consumer purchasing decisions. The method used in this research is a qualitative approach, where the author takes information from several sources as a basis for this research. The results of this research are that creativity and innovation greatly influence purchasing decisions. With Scarlett's various innovations and creativity, they are able to penetrate the international arena. To enter the international arena, a business must be able to handle every problem and be able to see existing opportunities, so that the company will be able to compete and do business internationally.